Behavioral activation for depression in groups embedded in psychosomatic rehabilitation inpatient treatment: a quasi-randomized controlled study - Melicherova, Ursula; Schott, Tobias; Köllner, Volker; Hoyer, Jürgen (Frontiers in Psychiatry, 2024)
Background: Behavioral activation (BA) and cognitive-behavioral therapy (CBT) have shown to be efficacious treatment methods for depression. Previous studies focused mostly on the outpatient treatment either in group or individual setting. The present study aimed at comparing the efficacy of group treatment BA vs. CBT , when embedded in inpatient psychosomatic rehabilitation treatment.Methods: 375 inpatients were randomly assigned to either BA (N = 174) or CBT (N = 201). We used established scales for depression such as the Beck Depression Inventory II (BDI-II, self-rating), the Quick Inventory of Depressive Symptomatology (QIDS; expert rating) and the Behavioral Activation for Depression Scale (BADS) to assess changes over the course of the treatment and at follow-up (4 to 6 months). In addition, we measured disability-related functioning with the Mini-ICF-APP, a rating scale built in reference to the International Classification of Functioning, Disability and Health (ICF). Multilevel models with repeated measures were conducted to examine the differences between groups in relation to change over time with patients' random effects.Results: Both group formats showed substantial reduction in depressive symptoms at the end of treatment (d= 0.83 BA vs. d= 1.08 CBT; BDI-II) and at follow-up after 4 to 6 months (d = 0.97 BA vs. d = 1.33 CBT, BDI-II; and d = 1.17 BA vs. d = 1.09 CBT, QIDS). There were no significant differences between treatment approaches. At least 50% symptom reduction was achieved by 53.7 % and 54.2 % in BA vs. CBT respectively. Reported activation levels increased from pre-to posttreatment (d = 0.76 BA vs. d = 0.70CBT), while showing loss of increment between the end of the treatment until follow up in both formats (d = 0.28 BA vs. d = 0.29 CBT).Discussion: Both modalities led to significant improvement of symptomatology and functioning at the end of the treatment and at follow-up, thus for the first time demonstrating the practicability of